PERFORMANCE OF BONDING MATERIAL IN SEMI-PRECAST CONCRETE SLAB - Doh, S.I.; Ideris, Z.; Narayanan, S.P; Kurian, V.J.; Gungat, L. (World Engineering Congress, 2007)
Bonding between old and new concrete is a potential area of research particularly in precast and semi precast construction. Precast and semi precast constructions are widely used in the industry because of advantages of labour reduction, short construction duration and cost effectiveness. The conventional cast in situ method forms a monolithic structure and is preferred. Many failures have occurred in slabs due to the debonding between the precast and cast in situ parts. The bond performance between the old and the new concrete plays an important role in the structural performance. Improper bonding between semi- precast concrete and cast in situ topping will cause relative shrinkage between them and finally lead to cracking that may promote the corrosion of steel reinforcement due to the penetration of chloride ions, water and other hazardous substances. Bonding also depends on the structuring of the fresh concrete in direct contact with the old surface. One precast and three semi precast slabs were cast first without bonding material (NB) and then with two different bonding materials namely cement slurry (CS) and SikaLatex (SIKA) applied between the precast and cast in situ topping. Semiprecast slab without bonding material and the precast slab were used as the control slabs. The effectiveness of different types of binder in bonding the new and the old concrete of slabs was studied by structural testing. The result is evaluated on basis of deflection and cracking behaviour of the slabs. The investigation revealed that the use of bonding material does not have very significant impact on the performance of the slabs.